Feasibility study of using waste badminton string fibers in concrete by morphological, microstructural and tensile characteristics - M, Kumaresan; S, Sindhu Nachiar; Sekar, Anandh (Revista de la Construcción. Journal of Construction, 2024)
As the strings are cut off from the badminton racquet system, the whole string will be replaced with a new one and there is no other alternative. Hence those cut-off strings are considered as waste and cannot be recycled, tons of waste are retained as debris. Among many research on recycled synthetic fiber, this application of waste material is a new context in sustainable construction. Here five different samples are examined based on wide usage, recycled Waste Badminton String Fiber (WBSF) is characterized and physically examined using a Scanning Electron Microscope, Fourier Transform Infrared Spectroscopy, and X-ray diffraction to use it as a recycled synthetic fiber in various fiber reinforced concrete applications. The diameter and cross-sectional area of WBSF are studied using the Scanning Electron Microscope imaging technique and Image J application, which shows that the fiber is highly engineered with 3 layers namely elasticity outer, outer layer, and core fiber with the mean diameter and net cross-sectional area is 777.6 µm and 5,05,959 µm2 respectively. The surface roughness of fiber is analyzed using ImageJ application which varies between 16-32 nm. The fiber samples are subjected to tensile loading the average tensile stress lies between 544.34 - 639.94 MPa. From the above examinations, the accurate diameter, net cross-sectional area, and voided area of the WBSF are calculated. The structural property and polymer relationship of the fiber are investigated using the X-ray diffraction technique and Fourier transform infrared spectroscopy, this reveals that the WBSF is of polyamide 6,6 form. The superior tensile stress compared to other recycled nylon fibers. So, the use of waste badminton string fiber in concrete is a new merging idea for fiber-reinforced concrete applications like pavements, pipes, tunnel lining, and other structural elements.